Ministry of Finance Decree No. 38 of the Year 2021 On the Advance Cargo Information (ACI) System = وزارة المالية قرار رقم 38 لسنة 2021 بشأن التسجيل المسبق للشحنات (ACI) - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic